Evaluating Low HER2 Status in Invasive Breast Carcinoma via HER2 Immunohistochemistry, with HER2 FISH Correlation: A Cohort of 112 Patients - Gokce Deniz Ardor; Miglena K. Komforti; Helena Hanna; Onur Ibanoglu; Abigail Lochala; Aziza Nassar (Hindawi-Wiley, 2023)
Introduction. Recent trials demonstrated clinically significant benefits in HER2-nonamplified breast cancer with HER2-low expression using novel anti-HER2 antibody-drug conjugates. Thus, HER2-low breast cancer was proposed as a separate diagnostic entity. Herein, we reclassify HER2-negative cancers according to the new HER2-low category using a modified system and further investigate HER2-very-low expression. Methods. 114 HER2 immunohistochemistry (IHC)-negative invasive breast tumors were identified from the pathology database of Mayo Clinic, Jacksonville, FL, between January 2019 and August 2022. Two blinded breast pathologists (BP) independently rescored HER2 IHC slides at 200x and 400x magnification. Discordant cases between the two BPs were rescored together. The most recent 2018 ASCO/CAP HER2 scoring criteria were used. HER2 (0) was subdivided into HER2 (absent) and HER2 (very low). HER2 FISH testing was performed in all cases. Results. The cohort comprised of 38 (33.3%) HER2 (0) and 76 (66.7%) HER2 (1+) tumors. The first round of rescoring at 200x and 400x magnification resulted in 17 (14.9%) HER2 (absent), 31 (27.2%) HER2 (very low), and 64 (56.2%) HER2 (1+) and 2 (1.8%) HER2 (2+) tumors by BP1 and 20 (17.5%) HER2 (absent), 33 (28.9%) HER2 (very low), and 61 (53.5%) HER2 (1+) tumors by BP2. The combined final rescoring by BP1 and BP2 was as follows: 15 (13.2%) HER2 (absent), 35 (30.7%) HER2 (very low), 63 (55.3%) HER2 (1+), and 1 (0.9%) HER2 (2+) cases. A comparison of the first round of rescoring between two BPs showed substantial agreement with Cohen's kappa value of 0.67. Both comparisons of first rescoring by BP1 and by BP2 to combined final rescoring showed almost perfect agreement with Cohen's kappa value of 0.83.Follow-up FISH studies showed one amplified tumor. Conclusion. Our data support the need for finer granularity, classification, and understanding of HER2-low breast cancers. We also show that reproducibility between trained BP can be obtained, albeit with scoring at high power and low threshold for showing challenging interpretations.